Digitalised Welfare-to-work program in Indonesia: A Prelimenary Study of The Pre-Employment Card (PECP) and Job-Loss Insurances (JLI) Programs - Fadillah Putra; Anwar Sanusi (Jurnal Studi Pemerintahan)
Unemployment is a serious challenge facing many countries around the world, including Indonesia. The government plays a crucial role in addressing this issue by implementing effective welfare-to-work (WTW) policies. This study examines the implementation of Welfare-to-Work (WTW) reform in Indonesia through an examination of the Pre-Employment Card Program (PECP) and Job-Loss Insurance (JLI) on unemployment figures. This study examines the use of digitalization in the implementation of the two programs. The study was conducted using qualitative methods with semi-structured interviews with a total of 37 participants (14 policymakers from the Ministry of Manpower and the Coordinating Ministry for Economic Affairs, 17 training providers related to the PECP and 6 participants). Secondary data was collected from previous studies with a total of 846 respondents. This study finds that digitalization can weaken jobseekers' motivation to access the full implementation of the WTW policy. The provision of helpdesks is beneficial for individuals who face difficulties in accessing digital services, especially those living in urban areas. However, digitization may not effectively support those who are geographically marginalized.